2017
DOI: 10.1177/0091552117743790
|View full text |Cite
|
Sign up to set email alerts
|

Performance Funding Policy Effects on Community College Outcomes: Are Short-Term Certificates on the Rise?

Abstract: Objective: Performance funding (PF) policies allocate a portion of state funding to colleges based on student outcomes. This study is the first to account for policy type and design differences, and explores the impact of performance funding on three levels of credential completions: short-term certificates, medium-term certificates, and associate’s degrees. Method: We create a panel dataset of 751 two-year colleges from years 1990 to 2013 using data from the Integrated Postsecondary Education Data System. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 33 publications
(38 reference statements)
2
49
0
1
Order By: Relevance
“…This boost in certificate production without concurrent increases in 2- and 4-year degrees raises concerns about the long-term impact of PBF policies since the returns for certificates are lower on average than those for associate’s or bachelor’s degrees (Belfield & Bailey, 2017). National DID analyses of multiple state PBF policies largely confirm null or negative findings from individual state studies for associate’s (Li & Kennedy, 2018; Tandberg et al, 2014) and bachelor’s (e.g., Tandberg & Hillman, 2014) degree production and an increase in short-term certificates (Li & Kennedy, 2018). One study found evidence that more recent PBF policies—those that tie performance funds to a college’s base funding rather than providing performance funds as an additional bonus—have a modest positive effect on degree production (Rutherford & Rabovsky, 2014).…”
Section: Case Studies Of Quasi-experimental Research In Educationmentioning
confidence: 85%
“…This boost in certificate production without concurrent increases in 2- and 4-year degrees raises concerns about the long-term impact of PBF policies since the returns for certificates are lower on average than those for associate’s or bachelor’s degrees (Belfield & Bailey, 2017). National DID analyses of multiple state PBF policies largely confirm null or negative findings from individual state studies for associate’s (Li & Kennedy, 2018; Tandberg et al, 2014) and bachelor’s (e.g., Tandberg & Hillman, 2014) degree production and an increase in short-term certificates (Li & Kennedy, 2018). One study found evidence that more recent PBF policies—those that tie performance funds to a college’s base funding rather than providing performance funds as an additional bonus—have a modest positive effect on degree production (Rutherford & Rabovsky, 2014).…”
Section: Case Studies Of Quasi-experimental Research In Educationmentioning
confidence: 85%
“…Tandberg et al (2014) found that associate degree production following PBF adoption increased in six states, decreased in four states, and did not change in nine states. A more recent study with a similar methodological design focused on the effects of PBF policies on credential completions at community colleges and showed that PBF policies, on average, were unrelated to changes in credential completions (Li & Kennedy, 2018).…”
Section: The Intended Outcomes Of Pbf Adoptionmentioning
confidence: 99%
“…Several quasi-experimental studies have employed a DD regression approach and shown that PBF can lead to increases in the production of short-term certificates rather than associate degrees (Hillman et al, 2015, 2018; Hu, 2019; Li & Kennedy, 2018; Li & Ortagus, 2019). Hillman et al (2018) examined two of the most robust PBF-participating states, Tennessee and Ohio, and found that Tennessee community colleges responded to PBF by producing more certificates rather than longer-term associate or bachelor’s degrees.…”
Section: The Unintended Consequences Of Pbf Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance funding–related research suggests that these incentive policies are marginally, if at all, effective in terms of improving the outcomes that are tied to funding. For example, little to no effect is observed for degree production or graduation rates for associate’s or bachelor’s degrees (Hillman, Tandberg, & Gross, 2014; Hillman et al, 2018; Hillman, Tandberg, & Fryar, 2015; Li & Kennedy, 2018; Rutherford & Rabovsky, 2014; Tandberg, Hillman, & Barakat, 2014; Tandberg & Hillman, 2014). However, some scholars find performance funding had led to increases in short-term certificates—credentials that are the simplest and fastest to produce (Hillman et al, 2018; Hillman et al, 2015; Li, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%